Curriculum Management in Improving Education Quality (Multisite Study on the S-1 PGMI Study Program at UIN Satu Tulungagung and the S-1 PGMI Study Program at UIN Maliki Malang - Agus Triani, Dewi; Qomar, Mujamil; Efendi, Nur; Hermanto, Mochamad (CV. Inara, 2025)
This study examines the strategies for curriculum planning, implementation, and evaluation in the S-1 PGMI study program at UIN Sayyid Ali Rahmatullah Tulungagung and UIN Maliki Malang to improve education quality. This qualitative research uses interviews, participatory observation, and document analysis. Data analysis is conducted through single-site and cross-site analysis, and data validity is tested through credibility, transferability, dependability, and confirmability. The findings show that the curriculum planning strategy integrates the administrative model and grassroots model through the formation of a curriculum development team, SWOT analysis, and curriculum preparation, which includes graduate profiles, Graduate Learning Outcomes (CPL), and course offerings. The implementation strategy uses the Enactment Curriculum approach and the Innovation Profile model (diagnosis, application, evaluation, follow-up). The evaluation strategy is conducted using the Outcome-Based Education (OBE) approach, which includes context, input, process, and product evaluation. Overall, these strategies are designed for adaptation to the challenges of the global era and to produce competitive graduates.